PEMELIHARAAN BENIH IKAN GURAME (OSPHRONEMUS GOURAMY) DENGAN FREKUENSI PEMBERIAN PAKAN YANG BERBEDA - Yudha Galih Wibawa; Mohamad Amin; Marini Wijayanti (Jurnal Akuakultur Rawa Indonesia, 2018)
ABSTRACT Feed management was a key factor influencing fish growth. One of the method that could be applied was the fish growth. The study aimed to determine the best of feeding frequency in rearing of gouramy fry. This research was conducted in February-March 2018 at Experimental Ponds Laboratorium of Aquculture Study Program, Faculty of Agriculture, Sriwijaya University. This study used a Randomized Completed Design (RCD) which consisted of four treatments and three replications, i.e provision of feed 2 times a day (P1), 3 times a day (P2), 4 times a day (P3), and 5 times a day (P4). The results showed that P3 (4 times a day) give the best values with the absolute weight, absolute length, feed efficiency and survival rate were 1.25 g, 1.63 cm, 90.86% and 98.89% respectively. The water quality parameters measured were temperature (26-29 oC), pH (6,5-6,7), dissolved oxygen (4,1-4,9 mg.L-1), and ammonia (0,03-0,011 mg.L-1).Keywords : Feed, Feeding frequency, Gourami fry, Growth